Produktivitas Induk dalam Usaha Ternak Kambing Lakor pada Kondisi Pedesaan di Pulau Lakor Kabupaten Maluku Barat Daya - Pitanlakor, Beni Markus; Jesajas, Heriyanus; Matitaputty, Procula.R. (Cangkok, 2024)
Parent Productivity in the Lakor Goat Farming Business in Rural Conditions on Lakor Island, Southwest Maluku Regency. This research was carried out in May-June 2023 in three villages, namely Letoda, Yamluli and Lolotwara villages. The method used was a survey of 30 Lakor goat breeder respondents who were determined using a simple random sampling method. The research results showed that the average weaning weight of the three sample villages, namely Yamluli Village, was 14.3kg, Lolotwara Village was 14.8kg and Letoda Village was 14.6kg; average body weight of goat kids aged 6-8 months from three sample villages, namely Yamluli Village 19.9kg, Lolotwara Village 24.3 kg and Letoda Village 23.6kg; types of forage in the form of banyan leaves, kusambi leaves and natural/field grass; the number of marriages/pregnancies from the three sample villages, namely Yamluli Village 1.5, Lolotwara Village 1.5, and Letoda Village 1.6 times, type of birth from the three sample villages was single 34.67%, twins 272% and triplets 48, 67%; litter size 3.79 tails, pre-weaning mortality 13.17%; The sex ratio of the three sample villages is Yamluli Village 2.1:2.2, Lolotwara Village 3.5-4 and 3.1:3.2 Tail Village and the lust cycle is 18-24 days. It was concluded that parent productivity in the Lakor goat farming business in rural conditions on Lakor Island, Southwest Maluku Regency is still good because even though the rearing of goats on Lakor Island is semi-intensive, the forage on Lakor Island really fulfills the livestock's needs, resulting in good productivity.